2007
DOI: 10.1002/adma.200701699
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Device Architecture for Highly Efficient Organic Light‐Emitting Diodes with an Orange‐Emitting Crosslinkable Iridium(III) Complex

Abstract: Transition-metal complexes in organic light-emitting diodes (OLEDs) can overcome the efficiency limit of fluorescent devices. Due to the strong spin-orbit coupling of these complexes, both singlet and triplet excitons can be harvested and an internal quantum efficiency of 100 % is possible.[1-3] Many complexes with transition-metals, such as iridium, ruthenium, osmium and platinum have been synthesized to develop highly efficient phosphorescent OLEDs (PHOLEDs), [4][5][6][7][8] because a simple ligand-variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 24 publications
1
84
0
2
Order By: Relevance
“…[136,137] Testing several materials in a multilayer device assembly, a maximum efficiency of 4.9% (at 100 cd m 2 ) could be realized. [137] Ulbricht and co-workers [138] and Rehmann et al [139] reported the synthesis of oxetane-functionalized bis-cyclometallated iridium(III) acetoacetate complexes and the optimization of multilayer OLEDs employing these emitters, which were covalently incorporated into a crosslinked matrix. The hole-transport layers (HTL) as well as the matrix of the EML consisted of oxetane-equipped tetraphenylbenzidine (TPD) derivatives, which were crosslinked by photo-induced cationic-ring-opening polymerization after deposition from solution.…”
Section: Complex-containing Polymers: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[136,137] Testing several materials in a multilayer device assembly, a maximum efficiency of 4.9% (at 100 cd m 2 ) could be realized. [137] Ulbricht and co-workers [138] and Rehmann et al [139] reported the synthesis of oxetane-functionalized bis-cyclometallated iridium(III) acetoacetate complexes and the optimization of multilayer OLEDs employing these emitters, which were covalently incorporated into a crosslinked matrix. The hole-transport layers (HTL) as well as the matrix of the EML consisted of oxetane-equipped tetraphenylbenzidine (TPD) derivatives, which were crosslinked by photo-induced cationic-ring-opening polymerization after deposition from solution.…”
Section: Complex-containing Polymers: Synthesis and Propertiesmentioning
confidence: 99%
“…While vapor-deposited devices often exhibit superior characteristics, solution-processed devices are catching up to show comparable performance. [138,[192][193][194][195][196][197] Besides the optimization of the employed layers, further technical approaches are pursued to improve the device outcoupling. [196,197] The application of transparent organic [198] or semitransparent metal cathodes [199] leads to so-called top-emissive devices with high power and EQE, which enables the fabrication of fully transparent displays and lighting devices.…”
Section: General Structure Of Oledsmentioning
confidence: 99%
“…To keep the technical aspects as consistent as possible with our earlier publications, and to show clearly the impressive improvements, we intentionally chose to use an established material set. The transfer to more recent materials in the field of polymer LEDs (e.g., better backbone polymers, triplet emitters [37] ) is straightforward, but it would be difficult to clearly differentiate and assign the improvements to the new concept alone. Please note that it is absolutely effectual to demonstrate the new concepts.…”
Section: à2mentioning
confidence: 99%
“…Eine Optimierung des Ladungstransports in der Matrix wurde durch Versetzen mit OXD-7 erzielt (siehe Hintergrundinformationen). [14] Zusätzlich wurden in der optimierten OLED QUPD [15] und OTPD [15] …”
Section: Triplettemitter Auf Basis Von Ptunclassified